Deixis Analysis in the Movie It Ends With Us: A Pragmatic Study - Salsadila, Silva; Ramadhanti, Nurul Fatimah; Afif, Nino Farisul; Rohbiah, Tatu Siti (Proceeding of Annual International Conference on Islamic Education and Language (AICIEL), 2025)
This research aims to analyze the types of deixis and their functions in the dialogue of It Ends With Us from a pragmatic perspective. This movie was chosen because it is an adaptation of a popular novel that displays emotional communication in audiovisual form. This research uses a descriptive qualitative method with the data source in the form of transcripts of the dialog of the main characters in the film. Data collection techniques were conducted through documentation and discourse analysis. The result shows that there are five types of deixis used in the dialog, namely persona, place, time, discourse, and social deixis. Persona deixis is the most dominant type, showing the relationship between the speaker and the interlocutor. Meanwhile, time and place deixis show the context of the situation underlying the conversation. Discourse and social deixis serve to strengthen the narrative structure and social relationships between characters. The use of deixis in this movie plays an important role in building meaning in accordance with the context of the scene and the emotions of the characters. This research contributes to the understanding of language use in film media as a means of contextual communication. The findings can also be a reference in the study of pragmatics, especially in the analysis of deixis in audiovisual texts.